The quality of life and comfort levels of hemodialysis patients with constipation: A descriptive and cross‐sectional study. Issue 3 (21st April 2022) - Bulbul, Elif; Cepken, Tugba; Caliskan, Ferda; Palabiyik, Birgul; Sayan, Canan; Kazancioglu, Rumeyza
Abstract: Introduction: This study was conducted to determine the constipation‐related quality of life, bowel habits, and comfort levels of constipated hemodialysis patients. It is known that the prevalence of constipation is high in hemodialysis patients. Methods: This was a cross‐sectional and correlational study. The study included 164 hemodialysis patients who were determined to have constipation by examining the constipation statuses of 385 patients based on the Rome‐IV criteria. The study was reported according to the STrengthening the Reporting of OBservational studies in Epidemiology Declaration. Findings: It was determined that as the constipation‐related quality of life of the patients increased, their comfort levels also increased. Constipation‐related quality of life increased in parallel with an increasing Bristol Stool Scale (BSS) score and an increasing number of bowel movements. The BSS scores of the patients were found to have a significant positive correlation with the patients' bowel movement frequencies and a significant negative correlation with their constipation frequencies. There was a negative correlation between years of dialysis and bowel movement frequencies. The presence of a previous gastrointestinal system complaint, the presence of an impact of constipation on the patient's dialysis session, and comfort levels were determined to be significant predictors of constipation‐related quality of life that explained 26.3% of the total variance in constipation‐related quality of life. Discussion: In patients receiving hemodialysis treatment, constipation is an important and frequently encountered problem. Constipation leads to a reduction in quality of life and hemodialysis‐related comfort.